2015
DOI: 10.21608/jpp.2015.51736
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF FOLIAR SPRAY WITH SOME MICRONUTRIENTS AND SLOW RELEASE NITROGEN FERTILIZERS RATES ON PRODUCTIVITY AND QUALITY OF SWEET POTATO (Ipomea batats L.).

Abstract: The present investigation was carried out at El-Bramoon Experimental Farm, Hort. Res. Institute, Mansoura, Dakahlia Governorate, Egypt (+ 7m altitude, 30 o 11latitude and 28 o 26 longitude), during seasons of 2012 and 2013, to study the effect of slow release-N Sulfur coated urea "SCU" rats, and foliar spray with some micronutrients levels as well as their interaction on productivity, and quality of sweet potato cv. Abees. The most important finding could be summarized as follows: In general, results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
3
2
0
Order By: Relevance
“…Overall means of Mn as affected by interaction between N forms and N rates indicated the superiority of urea over ammonium phosphate. These results confirmed those earlier obtained by Saif El-Deen et al, (2015) who found that Mn concentration in sweet potato tubers was increased with increasing N fertilizer rates up to 60 kg N fed -1 . They added that improvement of micronutrients content in tubers as well as yield may be attributed to stimulating biological activities, i.e., enzyme activity, chlorophyll synthesis, rate of translocation of photosynthetic products and increased nutrient uptake through roots after foliar fertilization.…”
Section: Manganese Mnsupporting
confidence: 92%
“…Overall means of Mn as affected by interaction between N forms and N rates indicated the superiority of urea over ammonium phosphate. These results confirmed those earlier obtained by Saif El-Deen et al, (2015) who found that Mn concentration in sweet potato tubers was increased with increasing N fertilizer rates up to 60 kg N fed -1 . They added that improvement of micronutrients content in tubers as well as yield may be attributed to stimulating biological activities, i.e., enzyme activity, chlorophyll synthesis, rate of translocation of photosynthetic products and increased nutrient uptake through roots after foliar fertilization.…”
Section: Manganese Mnsupporting
confidence: 92%
“…Enhanced root growth and function could improve nutrient and water uptake, supporting overall plant health and the production of more marketable tubers. The studies of Hartemink et al [18] and [12] were also documented the importance of nitrogen and foliar application of micronutrients for enhancing the marketable tubers yield in sweet potato and were agreement with present study.…”
Section: Effect Of Foliar Nutrition On Tuber Yield Marketable Tuber Y...supporting
confidence: 92%
“…Micronutrients like boron, zinc, and manganese play essential roles in various physiological processes necessary for tuber enlargement, aligning with the findings of Saif El-Deen et al [12] and [17].…”
Section: Effect Of Foliar Nutrition On Tuber Girth Length Tuber Bulki...supporting
confidence: 82%
See 2 more Smart Citations